Coach-initiated motivational climate and cohesion in youth sport - Eys, M. A.; Jewitt, E.; Evans, M. B.; Wolf, S.; Bruner, M. W.; Loughead, T. M. (Research Quarterly for Exercise and Sport, 2013)
Purpose: The general purpose of the present study was to examine the link between cohesion and motivational climate in youth sport. The first specific objective was to determine if relationships demonstrated in previous research with adult basketball and handball participants would be replicated in a younger sample and with a more heterogeneous set of sports. The second specific objective was to examine whether sources of athlete enjoyment moderate the relationships between motivational climate and cohesion. Method: Athletes (N = 997; 532 girls and 465 boys; M age = 15.26 ± 1.20 years) completed measures pertaining to coach-initiated motivational climate, cohesion, and sources of enjoyment. Results: Bivariate and canonical correlations revealed positive correlations between perceptions of a task-involving motivational climate and both task and social cohesion, while ego-involving motivational climate was negatively related. Cluster analyses suggested that individuals perceiving a low task-involving climate and high ego-involving climate perceived their teams as less cohesive. Finally, the degree to which participants derived enjoyment through other-referenced competency served as a moderator in the motivational climate-task cohesion relationship. Specifically, the relationship between task cohesion and motivational climate was more pronounced for those individuals who were less likely to derive enjoyment through other-referenced competency. Conclusions: Youth athletes' perceptions of coach-initiated motivational climate are related to cohesion. This relationship is, however, moderated by the degree to which athletes derive enjoyment through other-referenced competency. Motivational climate is an important variable to consider within team-building protocols intent on developing cohesion.